Judicial Invalidation of Ithbāt Nikāḥ Underage in the View of Religious Court Judges in Madura - M. Faiz Nashrullah; Abdul Rohim Al Wafi; Siah Khosyiah; Frilla Gunariah; Affan Najih Alghifary (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2025)
Underage ithbāt nikāḥ creates a legal loophole in Indonesia's Islamic marriage system. Child marriages that should require a dispensation are often legalized through ithbāt nikāḥ without such approval. This practice is prevalent in the Religious Courts of Madura, where most judges tend to grant petitions despite recognizing its contradiction with efforts to prevent child marriage. This study adopts a juridical-sociological approach through case analysis and in-depth interviews with judges. The findings show that rejection of underage ithbāt nikāḥ is rare, as judges prioritize protecting children's civil rights, such as birth certificates and legal family status. However, this generates a dilemma: granting applications risks legitimizing child marriage, while rejecting them may be seen as denying legal certainty for the community. As a middle path, some judges suggest alternatives, including recognition of children born out of wedlock, determination of child origin, and civil registration without marriage certificates. The study highlights the urgent need for clear legal guidelines to prevent misuse of ithbāt nikāḥ while ensuring child protection.